Disseminated Herpes Simplex Virus with Fulminant Hepatitis. (28th July 2015) - Rimawi, Bassam H.; Meserve, Joseph; Rimawi, Ramzy H.; Min, Zaw; Gnann, John W.
Abstract : Disseminated herpes simplex virus (HSV) is a rare cause of acute fulminant liver failure. We hereby present a case series of three patients with acute disseminated HSV with necrotizing hepatitis successfully treated with a week course of acyclovir. Early empiric administration of acyclovir therapy while awaiting confirmatory tests is critical in this potentially lethal disease.